2015
DOI: 10.1111/deve.12077
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Private‐Sector Tractor Service Provisions: Insights from Nigeria

Abstract: Agricultural mechanization has been integral to agricultural transformation during periods of development. Mechanization-service provisions can be constrained by economies of scale, seasonality, limited mobility, or heterogeneous inputs quality. However, information has been scarce regarding how the private sector has overcome these constraints especially in countries like Nigeria that are at low agricultural development stages. We present the results of a small survey of tractor owner-operators conducted in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
(35 reference statements)
6
34
1
Order By: Relevance
“…Similarly, higher farm wages for hired labor may induce adoptions of machines as substitutes at intensive margins. The existence of tractor owners among the sample within the same EAs is positively associated with machine adoption, consistent with earlier studies on SSA indicating the generally limited mobility of tractors beyond local areas (Takeshima et al 2015;. The greater use of irrigation and chemical fertilizer in the local area, which can also vary spatially, is also positively associated with machine adoptions, consistent with the hypotheses about the complementarity between yieldenhancing inputs and agricultural machines.…”
Section: Results Based On Glsssupporting
confidence: 87%
“…Similarly, higher farm wages for hired labor may induce adoptions of machines as substitutes at intensive margins. The existence of tractor owners among the sample within the same EAs is positively associated with machine adoption, consistent with earlier studies on SSA indicating the generally limited mobility of tractors beyond local areas (Takeshima et al 2015;. The greater use of irrigation and chemical fertilizer in the local area, which can also vary spatially, is also positively associated with machine adoptions, consistent with the hypotheses about the complementarity between yieldenhancing inputs and agricultural machines.…”
Section: Results Based On Glsssupporting
confidence: 87%
“…Cossar et al (2016) argued that private markets are better able to reach smallholder farmers than government programs in Ghana. Takeshima et al (2015b), focusing on Nigeria, found that farmers buying tractors from private markets are often more efficient than beneficiaries of tractors provided via government programs. Tractor owners who bought tractors from private markets provide services over longer distances, at a cheaper rate, and they also offer services during off-peak seasons.…”
Section: Myth or Reality? Governments Need To Import Tractors Becausementioning
confidence: 99%
“…They are proxied by the sample share (%) of farmers renting out tractors in the VDC and district where the smallholder is located, which is associated with the accessibility of tractor services. This indicator is used because tractor service provision is often limited to the locality of tractor owners (Takeshima, Edeh, et al., ; Takeshima, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“… The impact of mechanization on smallholders’ incomes is an important parameter of interest. Despite the growth of custom‐hiring services in many developing countries, including Nepal Terai, market failures may still be substantial because of the indivisibility of tractors and their relatively limited mobility in developing countries (Takeshima, Edeh, Lawal, & Isiaka, ), especially in Nepal Terai where most tractors are more expensive and bulky four‐wheel tractors, rather than two‐wheel tractors as in some other Asian countries (Takeshima, Adhikari, & Kumar, , Figure 2.1). The presence of such market failures suggests that the public sector can play a role in correcting such failures and improving the welfare of rural households. …”
mentioning
confidence: 99%